Bone mineral density and body composition in Australians following plant-based diets vs. regular meat diets - Austin, Grace; Ferguson, Jessica J. A.; Eslick, Shaun; Oldmeadow, Christopher; Wood, Lisa G.; Garg, Manohar L. (Frontiers in Nutrition, 2024)
Background & Aims: Bone mineral density (BMD) and body composition play an important role in maintaining metabolic health and physical functioning. Plant-based diets are known to be lower in protein and calcium which can impact BMD and body composition. This study aimed to investigate the relationship between various plant-based diets (PBDs) compared to regular meat-eaters on wholebody mineral density (BMD), body composition and weight status. Methods: A cross-sectional study of adults (n=240) aged 30-75yrs habitually consuming dietary patterns were recruited: vegan, lacto-vegetarian, pesco-vegetarian, semi-vegetarian, or regular meateater (48 per group). Parameters were measured via dual-energy x-ray absorptiometry (DXA) and multivariable regression analyses was used to adjust for lifestyle confounders, socioeconomic factors, and BMI. Results: After adjustments whole-body BMD and body composition was not significantly different between those following PBDs and regular-meat diets, except for lacto-ovo vegetarians who had significantly lower lean mass by -1.46kg (CI; -2.78, -0.13). Moreover, lacto-ovo vegetarians had a significantly lower T-score by -0.41 SD (CI;-0.81, -0.01) compared to regular-meat eaters. Waist circumference was significantly lower in individuals adhering to a PBD compared to regular-meat diet; vegans by -4.67cm (CI;-8.10, -1.24), lacto-ovo vegetarians by -3.92cm (CI; -6.60, -1.23), pescovegetarians by -3.24cm (CI;-6.09, -0.39), semi-vegetarians by -5.18cm (CI;-7.79, -2.57). There were no significant differences in lean mass (%), fat mass (% and total), android/gynoid measures, body weight or BMI across dietary patterns. All dietary patterns met the recommended dietary intake for calcium and protein, and 25-hydroxy-vitamin D status was comparable across groups.